Pengaruh Penyuluhan Menggunakan Media Phantom Gigi Terhadap Keterampilan Menyikat Gigi pada Siswa di MIN 29 Bireuen dan MIN 24 Bireuen - Rahma Waddah (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Dental and oral health is important for school-age children who are susceptible to caries. The prevalence of caries at the age of 10–14 years reached 63.8%, which includes ages 9–11 years. This high number is influenced by the low level of proper tooth-brushing skills. One effort to improve skills is through counseling using dental phantom media. The purpose of the study was to determine the effect of counseling using dental phantom media on tooth-brushing skills in students at MIN 29 and MIN 24 Birueun. This study used the Quasi Experiment method with a pretest and posttest non-Equivalent control group design. The population was all fourth-grade students of MIN 29 Birueun, totaling 47 students and MIN 24 Birueun, totaling 48 students. The study used the Lemeshow formula. so that the sample consisted of 32 students in the intervention group from MIN 29 and 32 students in the control group from MIN 24. The study was conducted on April 4–29, 2026. Data collection used an observation sheet for tooth-brushing skills. Data analysis using Paired Sample T-Test. The results of the study showed that the average pretest score of the intervention group was 39.94, the average posttest score of the intervention group was 72.88, the difference in mean values ​​was 39.94. The average pretest score of the control group was 44.16, the average posttest score of the control group was 64.66. The difference in mean values ​​was 20.5. Based on the Paired Sample T-Test, the significant value of the pretest and posttest was p = 0.000 <0.05. It can be concluded that there is an influence of counseling using tooth phantom media on tooth brushing skills in students at MIN 29 and MIN 24 Birueun. It is recommended that schools play an active role in improving students' dental health through routine education and collaboration with health workers